Role of Ayurveda with Multi modal Therapy in Prevention and Management of Autism Spectrum Disorders (ASD): The Whole System Approach - Renu Rathi1 , Bharat Rathi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Autism is a neuro-developmental ailment seen in the preschool age. It is a lifelong conditionand requires long term and multiple treatment interventions.Aim and Objective: To review and present a possible prevention and treatment protocol on Autism SpectrumDisorder (ASD).Material and Method: The present study is based on the literature search from Ayurveda compendia, recentpediatric textbooks, articles published in research journals from 1983 to 2019.Observations and Result: ASDs are the complex diseases with imbalance of Tridosha and Dwimanasdoshas(fundamental principles of body and mind), based on typical clinical features which match with DSM-V(Diagnostic and Statistical Manual) that can be correlated with Unmada (Psychosis/insanity). ASDs can beclassified into Autism, Asperger’s and Rett’s syndrome. The probable etiopathogenesis may be defectiveorganogenesis, brain damage, metabolic or genetic changes.Discussion: Acharya emphasized on Yuktivyapashray (rational therapy), Daiva vyapashray (nonpharmacological spiritual therapy) and Satvavajay chikitsa (Ayurveda psychotherapy) altogether in Unmadtreatment due to its complex nature. Recently developed therapies such as play therapy and cognitivebehavioral therapy-CBT can be a good adjuvant with Ayurvedic management of ASDs for better quality oflife.Conclusion: As no satisfactory treatment is available in modern medicine till now, multi-modal treatmentsuch as Ayurveda, behavioral therapy, physiotherapy, occupational therapy and early educational interventionsmight be beneficial to treat ASDs effectively. This review paper will be a torchbearer in the prevention andmanagement of ASDs with the whole system approach and proposed management algorithm.